Averting risk or embracing opportunity? Exploring the impact of ambidextrous capabilities on innovation of Chinese firms in internationalization. Issue 4 (3rd October 2016) - Zhou, Yu; Lu, Lu; Chang, Xiaoxi
Abstract : Purpose: The purpose of this paper is to examine the impacts of ambidextrous capabilities, explorative capability and exploitative capability on product innovation performance in the context of internationalization and cross-cultural environment; and to examine the moderating effects of CEO's preference of risks and opportunities in the international market on the relationship between ambidextrous capabilities and multinational enterprises' (MNEs) product innovation performance. Design/methodology/approach: Data were collected from 189 MNEs located in China, which develop international business through export, outsourcing, foreign equity investment or foreign direct investment. Measurement reliability and validity were examined and hierarchical linear regression was used to test the hypotheses. Findings: Results indicated that both explorative and exploitative capability are positively related to MNEs' new product development and commercialization of Chinese MNEs; and CEO's preference of risks and opportunities in international market plays a significant moderating role in the two phases of product innovation. Research limitations/implications: This study extends organizational ambidextrous capabilities theory to better understand the effects of explorative capability and exploitative capability on innovation performance in the context of internationalization and national cultural differences. Sample constitution is a possible limitation. Practical implications: MNEs, especially those from emerging economies, should develop both explorative and exploitative capability to be flexible and competitive in dealing with cultural differences. fully take risks and opportunities should be taken into consideration regarding the international market and national cultural differences, and take an effective contingency strategy, driven by the ambidextrous capabilities toward new product innovation development and commercialization. Originality/value: An empirical examination of how ambidextrous capabilities impact on Chinese MNEs' new product development and commercialization connects the organizational ambidexterity theory to the innovation and characteristics of upper echelons.